Next-generation sequencing identified SPATC1L as a possible candidate gene for both early-onset and age-related hearing loss. - Morgan, Anna; Vuckovic, Dragana; Krishnamoorthy, Navaneethakrishnan; Rubinato, Elisa; Ambrosetti, Umberto; Castorina, Pierangela; Franzè, Annamaria; Vozzi, Diego; La Bianca, Martina; Cappellani, Stefania; Di Stazio, Mariateresa; Gasparini, Paolo; et al. (Eur J Hum Genet, 2019)
Hereditary hearing loss (HHL) and age-related hearing loss (ARHL) are two major sensory diseases affecting millions of people worldwide. Despite many efforts, additional HHL-genes and ARHL genetic risk factors still need to be identified. To fill this gap a large genomic screening based on next-generation sequencing technologies was performed. Whole exome sequencing in a 3-generation Italian HHL family and targeted re-sequencing in 464 ARHL patients were performed. We detected three variants in SPATC1L: a nonsense allele in an HHL family and a frameshift insertion and a missense variation in two unrelated ARHL patients. In silico molecular modelling of all variants suggested a significant impact on the structural stability of the protein itself, likely leading to deleterious effects and resulting in truncated isoforms. After demonstrating Spatc1l expression in mice inner ear, in vitro functional experiments were performed confirming the results of the molecular modelling studies. Finally, a candidate-gene population-based statistical study in cohorts from Caucasus and Central Asia revealed a statistically significant association of SPATC1L with normal hearing function at low and medium hearing frequencies. Overall, the amount of different genetic data presented here (variants with early-onset and late-onset hearing loss in addition to genetic association with normal hearing function), together with relevant functional evidence, likely suggest a role of SPATC1L in hearing function and loss.

A novel deletion mutation involving TMEM38B in a patient with autosomal recessive osteogenesis imperfecta. - Rubinato, Elisa; Morgan, Anna; D'Eustacchio, Angela; Pecile, Vanna; Gortani, Giulia; Gasparini, Paolo; Faletra, Flavio (Gene, 2014)
Osteogenesis imperfecta (OI) is a hereditary bone disease characterized by decreased bone density and multiple fractures, usually inherited in an autosomal dominant manner. Several gene encoding proteins related to collagen metabolism have been described in some cases of autosomal recessive OI (including CRTAP, LEPRE1, PPIB, FKBP65, SERPINF1, BMP1, WNT1, FKBP10). Recently, TMEM38B, a gene that encodes TRIC-B, a monovalent cation-specific channel involved in calcium flux from intracellular stores and in cell differentiation, has been associated with autosomal recessive OI. Here, we describe the second deletion-mutation involving the TMEM38B gene in an 11 year-old Albanian female with a clinical phenotype of OI, born to parents with suspected consanguinity. SNP array analysis revealed a homozygous region larger than 2 Mb that overlapped with the TMEM38B locus and was characterized by a 35 kb homozygous deletion involving exons 1 and 2 of TMEM38B gene.
Keywords: Child; Chromosomes, Human, Pair 19; DNA Mutational Analysis; Exons; Female; Genes, Recessive; Homozygote; Humans; Ion Channels; Osteogenesis Imperfecta; Sequence Deletion